The Cyrcle of Microagression Among the Buginesse Adolescent: Examining the Influence of Experiences as a Victim, Observing, Listening to Microaggression Behavior Moderated by Understanding Microaggression - Umar, Nur Fadhilah; Manggau, Arifin; Hasim, Muhammad; Azzahrah, Humairah; Rafli, Muhammad (Bulletin of Counseling and Psychotherapy, 2025)
This study aims to investigate the direct and indirect relationship between experience as a victim, observation, and microaggression statements with Bugis regional microaggression behavior moderated by aspects of understanding microaggression in South Sulawesi. The study population was all Bugis students in South Sulawesi enrolled in the 2019/2020 academic year at public and private universities. The purposive sampling method was used to select 207 students who met the inclusion criteria. The instruments used consisted of adaptations of the Racial Microaggression Scale (RMAS) and the Bugis-South Sulawesi Regional Microaggression Scale. The results of data analysis using path analysis showed that experience as a victim of microaggression has a significant direct influence on Bugis regional microaggression behavior. Observation of microaggression also acts as a significant factor in reinforcing microaggression behavior. However, microaggression statements do not have a significant direct influence on microaggression behavior. Understanding of microaggression did not play a significant moderating role in the relationship between exogenous variables and microaggression behavior. These results demonstrate the complexity of the microaggression behavior phenomenon and suggest that there is a cycle to microaggression behavior that is similar to bullying. This cycle involves the roles of perpetrator, victim, bystander. Microaggression and bullying behaviors, although having different forms and expressions of behavior, have in common the impact of demeaning, harming, or discriminating against the victim and tend to occur repeatedly and consistently against the victim, reinforcing the cycle of microaggression behavior.